2021
DOI: 10.1039/d1sc00534k
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal-like bonding behaviors of a boron atom in a boron-cluster boronyl complex [(η7-B7)-B-BO]

Abstract: Boron displays many unusual structural and bonding properties due to its electron deficiency. Here we show that a boron atom in a boron monoxide cluster (B9O−) exhibits transition-metal-like properties. Temperature-dependent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…Numerous metal-doped boron clusters have also been produced and studied, significantly expanding the structural diversity of nanoborons. The study on transition-metal-doped boron clusters revealed the existence of various structures including metal-centered borometallic molecular wheels, metallo-boronanotubes, and metallo-borophenes. , The PrB 7 – cluster contains a half-sandwich structure featuring a B 7 3– moiety, which was also found recently in B 9 O – . Dilanthanide boron clusters were found to form inverse sandwiches, , while La 3 B 18 – features the first spherical trihedral metallo-borospherene …”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…Numerous metal-doped boron clusters have also been produced and studied, significantly expanding the structural diversity of nanoborons. The study on transition-metal-doped boron clusters revealed the existence of various structures including metal-centered borometallic molecular wheels, metallo-boronanotubes, and metallo-borophenes. , The PrB 7 – cluster contains a half-sandwich structure featuring a B 7 3– moiety, which was also found recently in B 9 O – . Dilanthanide boron clusters were found to form inverse sandwiches, , while La 3 B 18 – features the first spherical trihedral metallo-borospherene …”
Section: Introductionmentioning
confidence: 56%
“…The global minimum of B 7 – is a triplet with two unpaired electrons and a C 6 v structure . The closed-shell B 7 3– species is known to be doubly aromatic and forms half-sandwich type clusters, first observed in PrB 7 and recently in B 7 –B–BO – . , It has been used to design several binary clusters computationally. Thus, the stability of the C 6 v BiB 7 is a consequence of the high stability of the doubly aromatic B 7 3– species; the three 6p electrons participate in the π bonding with the B 7 moiety to fulfill the π aromaticity. Thus, the C 6 v BiB 7 can be viewed as [η 7 -B 7 3– ]­[Bi 3+ ], where the metallic bonding property of Bi is manifested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is illustrated in more detail in B 7 Pr, where the delocalized σ- and π-bonds give rise to the double aromaticity of B 7 3− , which is the driving force in shaping these concave structures since the B 6 ring is too small to incorporate the central B atom in B 7 3− . 103 In other words, the plunged central B atom shares its valence electrons with the B ring to fulfill double aromaticity, as very recently demonstrated by Tian et al 239 There are umbrella-type structures with several heavy atoms as well as Li and Al in the former case, and with Zr, Nb, Mo, Tc, and Sc in the latter. The B wheels arise either with a dimer along the symmetry axis or with the dopant atom at the center of the wheel as in B 8 Co − and B 9 Ru − , the first experimentally characterized B wheels.…”
Section: Discussionmentioning
confidence: 79%